2009
DOI: 10.1007/s10534-009-9280-x
|View full text |Cite
|
Sign up to set email alerts
|

The suitability of gallium as a substitute for aluminum in tracing experiments

Abstract: Aluminum is a toxic metal whose complex aquatic chemistry, mechanisms of toxicity and trophic transfer are not fully understood. The only isotope of Al suitable for tracing experiments in organisms-(26)Al-is a rare, costly radioisotope with a low emission energy, making its use difficult. Gallium shares a similar chemistry with Al and was therefore investigated as a potential substitute for Al for use in aquatic organisms. The freshwater snail, Lymnaea stagnalis was exposed to either Al or Ga (0.0135 mM) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Aluminum is without doubt the trivalent metal for which toxic effects are the best documented , due to acidification of natural waters which usually leads to an increase in total and free aluminum . However, for the reasons mentioned above, the study of its uptake mechanisms is a technical challenge and several workers have suggested using other trivalent metals as surrogates for Al 3+ . , Scandium (Sc) was selected for this study for two reasons. First, Sc 3+ and Al 3+ share many chemical similarities in addition to their (+III) oxidation state: they have an inert gas electronic configuration, they have a lack of redox capacities in biological systems, the solubilities of their ternary hydroxo-complexes are very similar and they are both class A metals that show preferential and similar affinities for hydroxide, fluoride, sulfate and phosphate .…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum is without doubt the trivalent metal for which toxic effects are the best documented , due to acidification of natural waters which usually leads to an increase in total and free aluminum . However, for the reasons mentioned above, the study of its uptake mechanisms is a technical challenge and several workers have suggested using other trivalent metals as surrogates for Al 3+ . , Scandium (Sc) was selected for this study for two reasons. First, Sc 3+ and Al 3+ share many chemical similarities in addition to their (+III) oxidation state: they have an inert gas electronic configuration, they have a lack of redox capacities in biological systems, the solubilities of their ternary hydroxo-complexes are very similar and they are both class A metals that show preferential and similar affinities for hydroxide, fluoride, sulfate and phosphate .…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that the suitability of Ga as a substitute for Al in biological systems seems to be controversial, since some authors agree 38 while others indicate different behaviours, 39,40 the 67 Ga radionuclide appears to be quite convenient for the bioassays it is herein expected to give some clue about the in vivo efficacy of the ligand to mobilize those metals.…”
Section: In Vivo Assaysmentioning
confidence: 99%
“…were determined by fitting analysis of the potentiometric data with the HYPERQUAD 2008 program. 27 Al 3+ and Ga 3+ hydroxide species [40][41][42] were included in the equilibrium complexation model and the species distribution curves were obtained with the HYSS program. 27…”
Section: Potentiometric Studiesmentioning
confidence: 99%
“…Whilst aluminum did not associate with MTs isolated from rat tissue (Vandervoet et al, 1992), there is some evidence of an association in the marine mussel, Mytilus galloprovincialis (Santiago-Rivas et al, 2007). Similarly, in the freshwater snail Lymnaea stagnalis, Al associates with heat stable proteins (the group to which MTs belong) to a greater extent than another hard metal Gallium (Walton et al, 2010). There is, however, no published evidence showing that Al itself increases the levels of expression of MTs or MTLPs in aquatic invertebrates.…”
Section: Introductionmentioning
confidence: 95%